2013
DOI: 10.17221/55/2013-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Regional assessment of forest effect on watershed hydrology: Slovakia as a case study

Abstract: ABSTRACT:Recently, the importance of forest effect on watershed hydrology has been increasingly recognized due to an elevated threat of floods and expected alterations of water regime in watersheds induced by climate change. We assessed the trade-off between natural conditions of 61 basic watersheds in Slovakia and expected water-regulatory capacity of forest in these watersheds. A multi-criteria decision-making scheme was proposed to calculate a coefficient for each watershed indicating the need to regulate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
1
2
0
1
Order By: Relevance
“…The study did not use hydrological model to relate the effect of forest cover with the surface runoff and river discharge. Nonetheless, results support the findings of Cui et al (2012); Hlásny et al (2013), Liu et al, 2016, Arceo et al (2018 on the regulatory effect of forest cover in the area. The study of Hlasny et al (2015) relates the effect of deforestation on decreasing the infiltration and evapotranspiration while increasing runoff while the studies of Khasanah et al 2010& Liu et al 2016 showed the positive effect of reforestation especially on hydrology.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The study did not use hydrological model to relate the effect of forest cover with the surface runoff and river discharge. Nonetheless, results support the findings of Cui et al (2012); Hlásny et al (2013), Liu et al, 2016, Arceo et al (2018 on the regulatory effect of forest cover in the area. The study of Hlasny et al (2015) relates the effect of deforestation on decreasing the infiltration and evapotranspiration while increasing runoff while the studies of Khasanah et al 2010& Liu et al 2016 showed the positive effect of reforestation especially on hydrology.…”
Section: Discussionsupporting
confidence: 88%
“…Watershed hydrological characteristics are used as bases for reports and evaluation of the watershed as watershed health is affected by land use, vegetative cover, and the interactions of both. Forest ecosystem regulates the water yield and water quality (Hlásny, Sitková, & Barka, 2013). Studies also show that stream flow pattern, magnitude, frequency and quality of most small watersheds are significantly affected by forest changes (Khasanah et al 2010;Cui, Liu & Wei, 2012;Liu et al 2016;& Arceo, Cruz, Tiburan, Jr., Balatibat, & Alibuyog 2018) and land use (Welde & Gebremariam 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hal ini menunjukkan bahwa sub DAS yang berhutan lebih mampu mengatur tata air dibanding dengan Sub DAS yang tidak berhutan. Hal ini sesuai dengan pendapat (Sylviani, 2008), hasil air dari hutan lindung lebih tinggi dari pada hasil air dari hutan tanaman; (Pudjiharta, 2008) kondisi hutan yang baik (kuantitas dan kualitas) hutan dapat meningkatkan fungsi hutan sebagai pengendali aliran; dan (Hlásny, Sitková, & Barka, 2013) menyatakan bahwa struktur dan distribusi hutan di dalam Daerah Aliran Sungai berpengaruh terhadap kualitas, kuantitas, dan kontinuitas air sungai.…”
Section: Curah Hujan Dan Kebutuhan Air Untuk Tanaman Padiunclassified